Logarithmic gradient estimates to a Monge-Ampere Type equation on \(S^n\) - Ye, Yunhua (Global Journal of Mathematical Analysis, 2015)
Monge-Ampere type equations arise naturally from many geometric problems. In this paper, we are concerned with one of these Monge-Ampere type equations on Â dimensional sphere \(S^n\)Â and obtain logarithmic gradient estimate by using Bernstein technique.